Role of Educational Institutions in Countering Extremist Narratives in Pakistan - Sadia Nasir (Journal of Political Studies, 2020)
The educational institutions have a multilayered relationship with extremism and can be very effective mechanism to counter extremism and in building counter extremist narratives. Nonetheless, this relationship has not been positively utilized nor the extremist exploitation of students in particular, has been systematically countered by the respective governments. Moreover, the problematic syllabus and regressive educational system facilitates extremist elements in recruiting new members and in dissemination of their narrative. While these educational institutions also have been soft targets for extremists. There is need to counter the extremist narrative through effective dissemination of national perspective of peaceful coexistence and tolerance towards diversity, while targeting emotional and logical appeal of the masses.